THE USE OF COLLABORATIVE CROSS-TEXT JIGSAW (CCTJ) IN TEACHING READING COMPREHENSION - Irma Putri Saifani; Dian Fajrina; Diana Achmad (LinguAmerta, 2025)
This quantitative study aims to explore the challenges faced by students in reading comprehension, with a particular focus on difficulties in identifying main ideas and understanding vocabulary. The research was conducted at MTsS Darul Ulum Banda Aceh and involved 31 eighth-grade students as participants. Data were collected using a combination of pre-tests, post-tests, and questionnaires to provide a comprehensive overview of students' reading comprehension skills. Initial findings from the pre-test indicated that many students struggled to recognize main ideas within texts and had limited vocabulary mastery, which hindered their overall understanding of reading materials. To address these issues, the Collaborative Cross-Text Jigsaw (CCTJ) strategy was implemented over five instructional meetings. This method emphasizes student collaboration and interaction through structured reading activities. The analysis of test results showed a significant improvement in students' reading comprehension abilities. The correlation value of 0.863 and a significance value of 0.000 (which is less than α = 0.05) indicate a strong and statistically significant positive relationship between the pre-test and post-test scores. Additionally, the questionnaire responses revealed that students found the CCTJ method engaging and supportive. They reported feeling more comfortable learning English, with better comprehension of the reading lo texts and increased enjoyment during the learning process.